2018
DOI: 10.3390/nano8121044
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte-Stabilised Magnetic-Plasmonic Nanocomposites

Abstract: In this work, new magnetic-plasmonic nanocomposites have been developed through the use of two complementary polyelectrolytes–polystyrene sulfonate (PSS) and poly(allylamine hydrochloride) (PAH). PSS, a negatively charged polyelectrolyte, was utilized as a stabiliser for magnetite nanoparticles, and PAH, a positively charged polyelectrolyte, was used to stabilize gold nanoparticles. The combination of these two entities resulted in a magnetic-plasmonic nanocomposite that is highly reproducible and scalable. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…All of these prove that PSS is successfully attached to the surface of nanoparticles. Moreover, the high zeta potential confirmed that the stability and dispersion of the nanoparticles were maintained due to the mutual repulsion between PGMNPs with high negative charge [38,39].…”
Section: Characterization Of Gmnpsmentioning
confidence: 97%
See 1 more Smart Citation
“…All of these prove that PSS is successfully attached to the surface of nanoparticles. Moreover, the high zeta potential confirmed that the stability and dispersion of the nanoparticles were maintained due to the mutual repulsion between PGMNPs with high negative charge [38,39].…”
Section: Characterization Of Gmnpsmentioning
confidence: 97%
“…1(a), GMNPs are functionalized with CTAB surfactants, next modified with PSS, and the modified GMNPs (PGMNPs) are conjugated with anti-digoxin antibody by physical adsorption. PSS has a very strong negative charge, so the steric hindrance and electrostatic repulsion between nanoparticles, and its corresponding monodispersity and stability can be effectively enhanced when PSS is coated on the surface [38,39].…”
Section: Assembly and Modification Of Gmnpsmentioning
confidence: 99%
“…PSS, a polyelectrolyte, played a pivotal role in this process. Initially, it accommodates silver ions (Ag + ) through electrostatic interactions during the synthesis phase and after the reduction of silver ions, PSS can stabilize the nanoparticles through various possible mechanisms, such as steric effects and potentially chemical bonding interactions (CHONG et al, 2020;STAFFORD;GARNIER;GUN'KO, 2018). The UV-Vis spectra (Fig.…”
Section: Synthesis and Characterization Of Ag-pss Nanohybridmentioning
confidence: 99%
“…The MNP coated with ionizable polymers, the so-called polyelectrolytes, has attracted great attentions recently [9,10]. In polar solvents such as water, their ionizable groups can dissociate, resulting in the formation of charges on the polymer chains and the release of counterions in solution.…”
Section: Introductionmentioning
confidence: 99%